Construction Learning Revolution: Optimizing Student Engagement and Understanding through Game-Based Learning with Minecraft as a Learning Medium - Koesalamwardi, Ario Bintang; Hansen, Seng (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2025)
In the digital era, innovative learning methods are key to increasing student engagement and understanding in engineering and construction. One of the increasingly emerging approaches is game-based learning (GBL), where games are used as interactive educational tools. This study explores the effectiveness of Minecraft: Education Edition in improving academic performance and engagement of students in the Construction Engineering and Management (CEM) Study Program at a university in Indonesia. This study used a mixed method, namely learning observation and questionnaire survey of students attending Minecraft-based lecture sessions. The findings of this study are presented in three main topics, namely the implementation of Minecraft: Education Edition as a learning medium, the Effectiveness of Minecraft as a Learning Medium for Construction Management, and implementation barriers. The results of this study are expected to provide insight into best practices in engineering education, especially in the application of interactive technology to improve learning effectiveness. This study also provides recommendations for higher education institutions to adopt game-based learning as part of innovative strategies in engineering learning. With increased student engagement and understanding through game-based simulations, Minecraft has the potential to be a revolutionary educational tool in the construction discipline.